Artérias da perna de Cebus libidinosus (Rylands, 2000) - Abreu, Tainá de (2013)
The aim of this work was to study Cebus libidinosus (C. libidinosus) leg arteries and compare those results with the literature available data for humans, chimpanzees and baboons. Were used 8 C. libidinosus specimens fixed in 10% fomaldehyde and 5% glycerin and stored in 10% formaldehyde. The leg supplying arteries originates from branches that occur in the thigh distal third and in the popliteal fossa. Thus, the femoral artery branches into popliteal and saphenous. The saphenous artery is well developed and subdivided into anterior, middle and low branches.These branches are responsible for foot vascularization. The popliteal artery originates common and fibular tibial arteries and vascularize the anterior and posterior regions. The common tibial artery branches into anterior and posterior tibial arteries. During eventual surgical interventions is important to avoid cuts in medial and posterior leg regions due the superficial paths of fibular and saphenous arteries.